The West Wing. The complete fourth season [videorecording (DVD)] - Sorkin, Aaron; Wells, John, 1956-; Lowe, Rob; Janney, Allison; Schiff, Richard, 1955-; Spencer, John, 1946-2005; Sheen, Martin; Channing, Stockard (West Wing, 2005)
Follows the re-election of President Bartlet to his second term and several crises both during and after the election in this 22-episode fourth season.